DPD Testing Before Treatment With Fluoropyrimidines in the Amsterdam UMCs: An Evaluation of Current Pharmacogenetic Practice - Martens, Forike K.; Huntjens, Daan W.; Rigter, Tessel; Bartels, Meike; Bet, Pierre M.; Cornel, Martina C. (Frontiers in Pharmacology, 2020)
The fluoropyrimidines (FP) (5-Fluorouracil, capecitabine and tegafur) are commonly used anti-cancer drugs, but lead to moderate to severe toxicity in about 10-40% of patients. DPD screening identifies patients at higher risk for toxicity who may be treated more safely with a lower drug dose. The Netherland's National guideline for colon carcinoma was updated in 2017 to recommend DPYD genotyping before treatment with FP. Pretreatment DPYD genotyping identifies approximately 50% of the patients, that will develop severe FP toxicity.Proper FP dose adjustment will reduce toxicity. The aim of the study was to assess the uptake of DYPD genotyping in the Amsterdam University Medical Centers and to evaluate stakeholder experiences to indicate barriers and facilitators of DPD screening implementation as routine clinical care.We used a mixed-method approach involving electronic patient records and pharmacy information systems analyses and fifteen semi-structured interviews with oncologists, pharmacists, and patients. The constellation perspective was used to identify barriers and facilitators at the level of practice, culture and structure.The proportion of FP users who were DPD tested before the start of their treatment showed an increase from 0% (0/32) in Q3-2017 up to 89% (32/36) in Q4-2018. Unlike a landmark paper published in 2015, the National guideline for colorectal carcinoma followed by meetings to achieve local consensus led to this steep increase in the proportion of patients tested.Facilitating factors for stakeholders to implement testing included the existence of clear protocols, (anecdotal) evidence of the utility, being aware that peers are adhering to standard practice and clear and simple procedures for ordering and reporting. Main barriers included the lack of clear divisions of responsibilities, the lack of consensus on a test approach, long turn-around times and non-user-friendly IT-infrastructures. More professional education on the utility and limitations of pharmacogenetic testing was desired by most stakeholders.While the evidence for DPD testing was sufficient, only after the update of a National guideline and local consensus meetings the proportion of FP users that were DPD tested before start of treatment rose to 89%. The implementation of personalized medicine requires stakeholders involved to attune practice, culture and structure.